Drugs and the politics of consumption in Japan - Vitale, Judith; Kadia, Miriam Kingsberg; Benesch, Oleg (Brill's Japanese studies library, 2023)
This book examines the history of drugs in Japan over four centuries, from the early modern period through the present day, showing how the definition, consumption, and regulation of substances both shaped and reflected trends in Japanese society